2018
DOI: 10.1016/j.jsps.2018.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructured liquid crystalline formulation as a remarkable new drug delivery system of anti-epileptic drugs for treating children patients

Abstract: Cubosomal-gel could be considered an innovative dosage-form for Cl through the transdermal route.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 56 publications
2
15
0
Order By: Relevance
“…The F1 formulation released 71 ± 4% of the drug after 4 h compared to 79 ± 8% from F2, and without any statistically significant difference (p < .05). Meanwhile, the F3 formulation and NT suspension showed lower NT releases of 30 ± 3 and 39 ± 1%, respectively, after 4 h. It can be seen that F1 and F2 provide a sustained release of NT, which agrees with a previous study that reported sustained drug release by cubosomes (El-Enin & AL-Shanbari, 2018). Interestingly, there was no burst release from the F1 and F2 formulations, also agreeing with reported studies that show drug release without a burst effect from cubosomes (Luechtefeld et al, 2016).…”
Section: In Vitro Releasesupporting
confidence: 90%
“…The F1 formulation released 71 ± 4% of the drug after 4 h compared to 79 ± 8% from F2, and without any statistically significant difference (p < .05). Meanwhile, the F3 formulation and NT suspension showed lower NT releases of 30 ± 3 and 39 ± 1%, respectively, after 4 h. It can be seen that F1 and F2 provide a sustained release of NT, which agrees with a previous study that reported sustained drug release by cubosomes (El-Enin & AL-Shanbari, 2018). Interestingly, there was no burst release from the F1 and F2 formulations, also agreeing with reported studies that show drug release without a burst effect from cubosomes (Luechtefeld et al, 2016).…”
Section: In Vitro Releasesupporting
confidence: 90%
“…They facilitate a more targeted and efficient brain delivery and reduce side effects at the same time [223]. The advantage of using nanotechnology-based drug delivery systems has been shown for different CNS indications, such as epilepsy, psychosis-related disorders and glioma [152,[223][224][225][226][227].…”
Section: Systemic and Cns Side Effectsmentioning
confidence: 99%
“…In previous studies, Nasr et al and Abo El-Enin et al found that the drug-loaded cubosomes were nearly spherical with irregular polyangular shapes. 10,37 This might be due to the GTP, which leads to a semi-cubic (semi-spherical) shape as it is reported in previous studies that GTP formed dense spherical nanoparticles. 50,51 The scanned cubosomes showed numerous water channels in their structure as the GMO is self-assembled in water and form a liquid crystalline cubic phase consisted of bicontinuous lipid bilayers with networks of water channels.…”
Section: Tem Imagingmentioning
confidence: 66%
“…Increasing the concentration of PF127 stabilized the system sterically and made an efficient distribution of the crystalline structure of the cubosomes. 36,37 Besides, increasing PF127 decreased the surface tension, which facilitated the formation of cubosomes with smaller PS. In a previous study, Abdelrahman, F.E.…”
Section: Characterization Of the Prepared In Situ Cubo-gels Ps Pdi mentioning
confidence: 99%
See 1 more Smart Citation